Mitotic arrest of breast cancer MDA-MB-231 cells by a halogenated thieno[3, 2-d]pyrimidine. Issue 8 (15th April 2015) - Ross, Christina R.; Temburnikar, Kartik W.; Wilson, Gerald M.; Seley-Radtke, Katherine L.
Graphical abstract